Implementasi metode karyawisata dalam pembelajaran pendidikan agama islam di smpit as-salam malang - Nisa’, Khoirotun (Maliki Interdisciplinary Journal, 2025)
This research aims to analyze the implementation of the field trip method in learning Islamic Religious Education (PAI) at SMPIT As-Salam Malang. The field trip method is used to provide a more contextual and in-depth learning experience for students by visiting places that are relevant to the learning material. This research uses a descriptive qualitative approach with data collection techniques through interviews, literature studies and documentation. The research results show that although the field trip method can improve students’ understanding of PAI material, there are several obstacles such as financial problems and students’ lack of focus on learning objectives during field trip activities. Implementation of this method is also faced with challenges in terms of careful planning and effective strategies to achieve educational goals. This research suggests the need for better strategies and adequate financial support to optimize the application of the field trip method in PAI learning at SMPIT As-Salam Malang.